Os efeitos da (in)tolerância política na participação em protestos no Brasil (2016 – 2019) - Sabrina Karlla Oliveira de Almeida (2021)
In recent years, Brazil has seen a surge in political protests, led by movements with differing agendas and grievances, and which is accompanied by an increase in attitudes of hostitlity between groups. The present study investigates whether, and how, (in)tolerant attitudes are linked to political engagement – more specifically, to protest activity – and the costs and effects these attitudes may have on a democratic system. The study employs a multivariate approach on data from Lapop (2016-2017; 2018-2019) and Datafolha (2019) to test whether (in)tolerance leads to participation in protests, and how a group’s chances of participation are affected by it’s position on a spectrum of (in)tolerance, and by it’s democratic preferences and principles. The study’s hypothesis is that political (in)tolerance varies according to group’s relations and configurations, and thus does not directly affect participation in protest, if considered in isolation. (In)tolerance is related to the perceived costs of tolerating rival political groups and, in turn, these costs determine individual propensity to (in)tolerant attitudes, which affect political engagement. General results of this inquiry indicate that the identity of groups to whom (in)tolerance is directed and the group’s identity adherence to democratic principles are frequently connected to (in)tolerant attitudes and protest involvement. I argue, therefore, that the effects of (in)tolerance can only be adequately understood, and measured, when one takes into account which groups and behaviors are tolerated or not, and for what reasons.